Action Organization Analysis: Extending Protest Event Analysis Using Hubs-Retrieved Websites. (May 2018) - Kousis, Maria; Giugni, Marco; Lahusen, Christian
The comprehensive and systematic study of collective action organizations (AOs) requires a new methodological approach that takes into account the rise of online sources as well as the new ways in which people interact and participate in politics. This article aims to present and situate in the related literature such an approach, which was recently created and applied in two European Commission funded research projects, LIVEWHAT and TransSOL, across nine and eight countries respectively. Moving beyond recent studies using online sources, our research used a hubs website based approach to study alternative action organizations (AAOs) in the LIVEWHAT project and transnational solidarity AOs in the TransSOL project. The hubs and subhubs websites that aggregate data on AOs in multiple regions were scraped to identify national samples that offer advanced coverage of the repertoire of AO activities, as defined by the teams. These nodal websites were used as sources, similar to the way in which newspapers are treated in protest event analysis. The article situates and compares the new action organization analysis approach against its foundational protest event, protest case, and political claims analyses, as well as other approaches offering data on online activism. It outlines its main features and the related data construction process, while showcasing its application in the two European Commission cross-national projects. Finally, its merits and limitations are discussed, including a reference to how it can be used as a foundation for a mixed-methods approach.